Value Creation in Innovations Crowdsourcing. Example of Creative Agencies - Agafonovas, Andrius; Alonderienė, Raimonda (Organizations and Markets in Emerging Economies, 2013)
Innovations are crucial for most of the companies to survive. However, the concept of innovation has become broader, including new forms of open innovation, such as crowdsourcing. The aim of this paper is to define the business model of a crowdsourcing-driven organization to create value. Empirical research consists of case studies on current crowdsourcing platforms, focus groups with potential crowd members and in-depth interviews with potential customers of creative agencies. Best practices were combined with solutions for closing the most significant gaps in order to create a successful business model. The developed model suggests separating the crowd into free users and an empowered core team and enabling collaboration. Moreover, an innovative motivational model is introduced. Due to a three-step sequence of solution/idea generation, superior value is proposed to the customer. Another competitive advantage should be flexibility and adaptability to the customer’s needs. The paper is original since extended analysis of all crowdsourcing stakeholders is delivered. It also has practical value proposing a business model for creative agencies.
Keywords: crowdsourcing; innovations; creative agency; business model; value creation